دور الحوكمة الحضرية المحلية في تحقيق التنمية المستدامة في الجزائر The role of local urban governance in the achievement of sustainable development in Algeria - طواهرية أمال (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
ملخص تهدف الورقة البحثية الى تسليط الضوء على دور الحوكمة الحضرية المحلية في تحقيق التنمية المستدامة في الجزائر و هذا من خلال تناول الإطار النظري و المفاهيمي للمصطلحين و محاولة ضبطهما ، إضافة الى إبراز العلاقة بين مفهوم الحوكمة الحضرية المحلية و كيف تساهم هذه الأخيرة في تحقيق التنمية المستدامة في الجزائر وفي هذا السياق اعتمدنا على الإشكالية الآتية : ما هو دور الحوكمة الحضرية المحلية في تجسيد التنمية المستدامة في الجزائر؟ وللإجابة على هذا الإشكال انطلقنا من فرضية رئيسية مفادها آن هناك علاقة تفاعلية وظيفية بين مفهوم الحوكمة الحضرية على الصعيد المحلي تؤثر على مؤشرات التنمية المستدامة .، وللتحقق من هذه الفرضية اعتمدنا المنهج الوصفي التحليلي ، لوصف متغيرات الدراسة و تحليلها ،وعليه توصلنا الى إثبات الفرضية حيث يتضح جليا انه كلما تحققت مؤشرات الحوكمة الحضرية علي الصعيد المحلي كلما ساعد ذلك على تحقيق التنمية المستدامة . Abstract The research paper aims to highlight the role of local urban governance in achieving sustainable development in Algeria by addressing the conceptual and conceptual framework of the two terms and attempting to control them. It also highlights the relationship between the concept of local urban governance and how the latter contributes to sustainable development. In this context, we have relied on the following problems: What is the role of urban governance in reflecting sustainable development? In response to this problem, we have proceeded from a key premise that there is a functional interaction between the concept of urban governance at the local level that affects indicators of sustainable development. And to verify this hypothesis, we adopted the analytical descriptive approach to describe and analyze the study’s variables. and therefore we have come to prove the hypothesis, where it is clear that the more urban governance indicators are achieved the more this helps achieve sustainable development